2018
DOI: 10.1002/chem.201800405
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Activation of Coordinated Dinitrogen with p‐Block Lewis Acids

Abstract: This Concept article highlights recent research on Lewis acid adducts of dinitrogen complexes, including our contributions. After a reminder of the early works, it is demonstrated that such kind of species offers a new platform for dinitrogen functionalization as well as valuable models for the understanding of elementary steps of (bio)catalytic cycles. When possible, parallels regarding this mode of activation from the orbital point of view are drawn between the different systems discussed herein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 85 publications
0
21
0
Order By: Relevance
“…In addition, it should be noted that, beyond direct N 2 transformation to another chemical entity, Lewis acid binding to metal‐coordinated N 2 is key to further increase the charge delocalization from the metal to the N 2 moiety and, hence, enable its catalytic transformation, as recently by Simonneau and Etienne [21] …”
Section: Associative Pathwaysmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, it should be noted that, beyond direct N 2 transformation to another chemical entity, Lewis acid binding to metal‐coordinated N 2 is key to further increase the charge delocalization from the metal to the N 2 moiety and, hence, enable its catalytic transformation, as recently by Simonneau and Etienne [21] …”
Section: Associative Pathwaysmentioning
confidence: 97%
“…Other bond‐forming reactions with elements such as boron, phosphorous or with other Lewis acids are excluded from the scope of the current Review as their scarcity complicates the possibility to draw mechanistic conclusions. The interested reader may refer to the recent reviews from Chirik and co‐workers [19] and Simmoneau and Etienne, [21] which provide a good overview on the recent research in the field.…”
Section: Introductionmentioning
confidence: 99%
“…This 31 P NMR resonance was broadened at 298 K; this suggests fluxionality within complex 2, which was confirmed by low temperature NMR spectroscopy, 5and 159.6(5) °], which is typical for Lewis acid-functionalised N2 ligands. 19 The cis geometry of this bending around Mg is unique to 2 (compared to the other crystallised Co species 6,18 ), but this is just in the solid state. It is likely that 2 is fluxional in solution, as evidenced by the variable temperature 31 P NMR spectroscopy ( fig.…”
mentioning
confidence: 99%
“…154 They had previously demonstrated by orbital analysis 155 a possible increased reactivity of the terminal nitrogen atom of ( 63) towards electrophiles and later showed that these reactions divided into two broad classes: addition reactions 156,157 or Lewis acid-base interactions. In order to better apprehend the reactivity of the N2 ligand in (63), the interaction with group 13 LAs [GaMe3, AlMe3 and B(C6F5)3] was explored. The 1:1 reaction of these LAs with (63) 66) exhibited two resonances; an upfield resonance corresponding to the shielded bridging N (Nα) and a downfield resonance assigned to the terminal N (Nβ).…”
Section: Adducts Of P-block Lewis Acids With End-on Side-on Bimetallic Dinitrogen Complexesmentioning
confidence: 99%
“…In a final section, pieces of work issued from main group chemistry and relevant in the context of N2 push-pull activation will be presented. 63,64…”
Section: Introductionmentioning
confidence: 99%